Prinsip dan Hukum Perkembangan Peserta Didik di Jawa Timur - Habsy, Bakhrudin All; Rahmawati, Alya; Azmil, Ulil; Livi, Ratna Nur (AHKAM, 2023)
Development is a process of change in an individual over time, influenced by maturity and interaction with the surrounding environment. This developmental process can be understood through certain laws and principles. These laws and principles regulate all aspects of an individual's development and are always present in the developmental process. Therefore, these laws and principles should be understood by all stakeholders in education, especially educators or teachers. Because these principles are crucial in improving the effectiveness and efficiency of achieving educational goals, developing the curriculum, and even creating learning programs according to the needs of students. Students often have different learning styles. Teachers also have the responsibility to guide and mentor students to develop in a gradual, organized, and non-deviating manner.